The effect of the heat flow amount and continuity on dried rice quality - Mojsovski, Filip; Dimitrovski, Dame (Faculty of Mechanical Engineering, Ss. Cyril and Methodius University in Skopje, Republic of North Macedonia, 2020)
A research was conducted through field tests on mixed-flow rice dryer. The realization of the planned study was carried out by applying intermittent system of drying and selection of correct drying conditions. The heat flow amount and continuity were observed and evaluated in multi-thermal zoned drying process. Hot air temperatures, up to 45 oC, were used. Paddy from local rice varieties, with the initial moisture content, wet basis, up to 26 %, was processed to the desirable final moisture content, from 8% to 12%. Reached at three levels, the final moisture content depends on intended rice use: 1) for sale, 2) for one year storage and 3) for five years storage. The effect of drying air temperature level, heat flow intensity and retention time duration on dried paddy quality was analyzed.
Keywords: drying; mixed-flow dryer; intermittent drying; paddy